THE EFFECT hCG (human Chorionic Gonadotropin) TO OVULATION AND HATCHING OF FISH EGGS - Martiani Harianja; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted for 30 days, from 20 Januari to 19 Maret 2017 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Science, University Of Riau, The Purpose of his study was to research the effect of the hCG (human Chorionic Gonadotropin) dose on ovulation eggs, eggs diameter, and hatching fish eggs. The method used in this research is descriptive method with one factor, four treatment and two replications. The treatment used is as follows : PO Control using NaCL 0,9 % as much 1 ml/kg weight of test fish. P1 : Injection of hCG with dose 700 IU/kg weight of test fish. P2 : Injection of hCG with dose 900 IU/kg weight of test fish. P3 : Injection of hCG with dose 1100 IU/kg weight of test fish. The best result of the research is P2 : Injection of hCG with dose 900 IU/kg weight of test fish the with an average latent time 7 hours and 2 minutes, amount eggs(items)/g 369 items, increase in egg diameter 0,2 mm, IOS 13,68 %, Fertilization Rate 73,85 %Hatching Rate 74,47 %, Survival Rate (SR4) 71,43 %Keywords : Fish ingir-ingir (Mystus nigriceps), Hormon hCG, Ovulation, Survival